BS EN ISO 21219-16. Intelligent transport systems. Traffic and travel information (TTI) via transport protocol exports group, generation 2 (TPEG2). Part 16. Fuel price information and availability (TPEG2-FPI) (28th July 2020) - British Standards Institution,
No abstract available